Can the publication of guidelines change the management of early rheumatoid arthritis? An interrupted time series analysis from the United Kingdom - Judge, A; Wallace, G; Prieto-Alhambra, D; Arden, NK; Edwards, CJ (Oxford University Press, 2015)
Objective. To assess whether publication of national treatment guidelines improved the management of early RA in the UK.